2015
DOI: 10.1111/jebm.12170
|View full text |Cite
|
Sign up to set email alerts
|

The value of patient selection in demonstrating treatment effect in stroke recovery trials: lessons from the CHIMES study of MLC601 (NeuroAiD)

Abstract: ObjectiveThe CHIMES Study compared MLC601 to placebo in patients with ischemic stroke of intermediate severity in the preceding 72 hours. We aimed to verify if patient selection based on two prognostic factors (ie, stroke severity and time to treatment) improves detection of a treatment effect with MLC601.MethodsAnalyses were performed using data from the CHIMES Study, an international, randomized, placebo‐controlled, double‐blind trial comparing MLC601 to placebo in patients with ischemic stroke of intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…We recently showed that subjects with moderately severe stroke and/or longer stroke OTT improve the power of detecting differences in recovery between treatment groups at 3 months [9]. In this present analysis, NIHSS score and OTT individually improve the power even more after longer observations of up to 18 months, and NNT is low and stable over time, especially in subjects with more severe strokes.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…We recently showed that subjects with moderately severe stroke and/or longer stroke OTT improve the power of detecting differences in recovery between treatment groups at 3 months [9]. In this present analysis, NIHSS score and OTT individually improve the power even more after longer observations of up to 18 months, and NNT is low and stable over time, especially in subjects with more severe strokes.…”
Section: Discussionmentioning
confidence: 55%
“…We have identified several factors that predict poorer outcomes at 3 months, namely older age, female sex, worse baseline stroke severity and longer delay between stroke onset and initiation of treatment [6,8,9,10,15]. The same factors were reported in many in other previous studies [16,17,18,19,20,21,22] and were also found to predict deterioration at 1 and 5 years after a stroke [7,12,22,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional Chinese Medicine (TCM) has been historically used for stroke treatment, and is widely used today. [ 7 ] Chinese herbal medicine is an important component of TCM, which has several characteristics, including natural medicine, complex composition, and multifunction.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical evidence base for the efficacy and safety of MLC601 after acute ischemic stroke is provided by the large CHInese Medicine NeuroAiD Efficacy on Stroke Recovery (CHIMES; ClinicalTrials.gov: NCT00554723) and CHIMES-Extension (CHIMES-E) Studies [9,10]. In a post-hoc analysis, MLC601 showed a favorable effect on post-stroke recovery at 3 months in patients with persisting and/or moderately severe neurological deficit [11]. It also showed significant benefit (mRS < 1) at 6 months persisting up to 18 months [10], providing clinical evidence that supports the pre-clinical studies demonstrating neurorestorative effects.…”
Section: Introductionmentioning
confidence: 99%